The Effect Of Current Ratio, Inventory Turnover, And Debt To Equity Ratio On PT. Indofood CBP Sukses Makmur Tbk Period 2011-2020 - Subhan Subhan (International Journal of Economics, Business and Innovation Research, 2023)
The purpose of this study is to see the effect of the Current Ratio Inventory Turnover and Debt To Equity Ratio on Return On Assets at P.T. Indofood CBP Sukses Makmur Tbk Period 2011-2020. The results of the study Partially Partial Inventory Turnover (ITO) had no significant effect on Return On Assets (ROA) based on the results of the t-test, it showed that the value of t count < t table or 0.295 < 2.447 with a significant value greater than alpha or 0.0778 > 0,05. Partial Inventory Turnover (ITO) has no significant effect on Return On Assets (ROA) based on the results of the t-test showing that the value of t count < t table or 0.295 < 2.447 with a significant value greater than alpha or 0.0778 > 0.05. Partially Debt to Equity Ratio (DER) has a significant effect on Return On Assets (ROA) based on the results of the t-test showing that the value of -t count < -t-table or -12.067 < -2.447 with a significant value smaller than alpha or 0.000 < 0, 05. Simultaneously Current Ratio (CR), Inventory Turnover (ITO), and Debt to Equity Ratio (DER) to Return On Assets (ROA) at the company P.T. Indofood CBP Sukses Makmur Tbk period 2011-2020 based on the results of the F test showed that the calculated F value > F table or 58.762 > 4.7570 with a significantly smaller value than alpha or 0.000 < 0.05. The magnitude of the simultaneous influence between Current Ratio (CR), Inventory Turnover (ITO), and Debt to Equity Ratio (DER) to Return On Assets (ROA) at PT. Indofood CBP Sukses Makmur Tbk for the 2011-2020 period based on the Summary table is determined by the R square value of 0.967, meaning that the contribution of the variable Current Ratio (CR), Inventory Turnover (ITO) and Debt to Equity Ratio (DER) to Return On Assets (ROA) is equal to 96.7% and other variables determine the remaining 3.3